2019
DOI: 10.7759/cureus.6201
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Risk Factors Associated with Fatal Drowning Accidents in the Paediatric Population: A Review of International Evidence

Abstract: Introduction: Evidence from Ireland’s Childhood Mortality Register demonstrates that drowning is the second leading cause of death in children. It occurs more commonly in adolescent males engaged in summer water-based activities and in children aged 1-4 years with access to swimming pools/unprotected water sources. Despite being an island nation, a significant lack of guidelines exists to reduce drowning accidents in these at-risk populations.Aim: Review international evidence surrounding risk factors associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
3
9
0
1
Order By: Relevance
“…In this study children were in the high-risk group, and the highest frequency referred to two-year-old children. Almost similar results were found in a study held in Ireland by Davey et al showed that the majority of drowning cases affected children between the ages of 1-4 ( 8 ), other studies held by Evans et al ( 9 ), Denny et al ( 10 ), Wang et al ( 11 ), and Raess et al ( 12 ) showed that drowning mostly affected children under the age of 5 which comes in agreement with our findings. This result may have been caused by the absence of children strict supervision.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study children were in the high-risk group, and the highest frequency referred to two-year-old children. Almost similar results were found in a study held in Ireland by Davey et al showed that the majority of drowning cases affected children between the ages of 1-4 ( 8 ), other studies held by Evans et al ( 9 ), Denny et al ( 10 ), Wang et al ( 11 ), and Raess et al ( 12 ) showed that drowning mostly affected children under the age of 5 which comes in agreement with our findings. This result may have been caused by the absence of children strict supervision.…”
Section: Discussionsupporting
confidence: 93%
“…This result is caused mainly because of swimming activities held during summer time with the lack of swimming ability among certain age groups. Several studies conducted in Ireland, France, Australia and china by Davey et al ( 8 ), Bessereau et al ( 18 ), Leavy et al ( 19 ) and Liu et al ( 20 ) respectively, together with a study held by Loux et al ( 21 ) revealed that summer was the season with the highest percentage in regards to risk factors associated with fatal drownings compared to other months of the year which came out with agreement with the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The AAP strongly advises that parents practice “touch supervision” for young children, where they can be immediately reached at all times around or in bodies of water, baths, or swimming pools. 20 , 21 Adult supervision is especially essential in the vicinity of pools, particularly those with no installed security measures. We found that most severe drowning events (18 out of 22) that were complicated with neurological outcomes or death occurred in private pools.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been limited European studies on drowning, and only one has reported a Mediterranean case series with environmental characteristics similar to ours. 3,7,13 In these studies, the authors have reported more adverse outcomes, including a higher need for CPR and deaths. However, this can be partly explained by a larger number of tourists rather than resident children in their samples.…”
Section: Keynotesmentioning
confidence: 99%